A system approach to enterprise organization with an application to Telkom - Acton, Mark (Department of Mechanical Engineering, 2016)
The argument of this dissertation is that some of the dilemmas faced by enterprises today are a consequence of the 'authoritarian mode'1 in which enterprises are organized. The 'authoritarian mode' of organization has the assumptions of the mechanistic world view (paradigm) as its basis. These assumptions are however not relevant in fast changing and complex environments such as that which enterprises must deal with today. It is argued that an alternative paradigm is required to resolve the dilemmas faced by enterprises organized in the 'authoritarian mode'. The dissertation presents an 'empowerment and alignment' 2 mode of organization which has the social systems paradigm as its basis. The social systems paradigm has a significantly different set of assumptions about the nature of reality compared to the mechanistic paradigm. It is proposed that this more appropriate set of assumptions will resolve the current dilemmas which mechanistically organized enterprises are experiencing. A real world organization (namely Telkom Network Build) is used to practically demonstrate the above mentioned ideas. It is argued that Telkom Network Build is operating in the 'authoritarian mode' and that this is the underlying cause of a number of dilemmas of organization. A proposed conceptual design for the organization of Telkom Network Build division in the 'alignment and empowerment' mode is presented. The proposed design has the assumptions of the social systems view of reality as its basis.